Ligaya ng wika "kilos-kilos' an interactive multi-sensory activity kit for parents and teachers to teach Filipino as a first language and create an early exposure to the language among children between the ages 0 to 3, in the home and extending to the preschool of Playscape Early Learning, Rockwell - Tan, Isabela Maria; Reyes, Mitzi Marie Aguilar (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
As mandated by the Bilingual Policy of 1987, upon entering the first grade, Filipino is instated as a subject in the educational curriculum. It is taught as a first language, and for children, specifically those entering private school, who have no prior exposure or practice in using the language. this proves to be difficult. There have been several accounts of Filipino children, as they enter formal education, who have to take Filipino language together with foreigners, due to the lack of experience and practice in using the language. The government has made efforts in introducing the Filipino language to children at an earlier age. In 2009, the Department of Education instilled the Mother Tongue-Base Multilingual Education (MTB-MLE), which states that preschool teachers will use the mother tongue or first language of the children as the medium of instruction. However, private schools have the liberty to steer away from the guidance of the Department of Education, and an evaluation by the National Commission for Culture and the Arts (NCCA) revealed that the program is not seriously implemented by private school institutions Several publishing houses have also released board books to teach early Filipino concepts to children. However, none in the local context have explored the use of interactive, and multi-sensory elements, like lift-a-flap, touch-and-feel, music buttons, and pop-up mechanisms, which several children seek in early literature. This study aims to explore the incorporation of interactive, and multi-sensory design, in creating a medium that will engage children to learn the Filipino language, through the facilitation and guide of parents and teachers.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 267-268.
Keywords: Filipino language; Language acquisition